Long-term thermal stabilities of ammonium ionic liquids designed as potential absorbents of ammonia. Issue 51 (6th May 2015) - Lorenzo, M.; Vilas, M.; Verdía, P.; Villanueva, M.; Salgado, J.; Tojo, E.
Abstract : Searching for potential absorbents in working pairs with NH3, a series of new ammonium ionic liquids related to choline, were designed and synthesized. Their thermal stabilities in both non-isothermal and isothermal conditions were studied. Abstract : Searching for potential absorbents in working pairs with NH3, a series of new ammonium ionic liquids related to choline were designed and synthesized. In order to explore their applicability in refrigeration by absorption, their thermal stabilities were studied. For this proposal, a thermogravimetric analyzer, TGA 7 – Perkin-Elmer, was used in dynamic mode from 100 °C to 800 °C at 10 °C min −1 under dry air atmosphere. From the ionic liquids TG curves, the onset temperatures ( T onset ) were determined, as well as the loss of mass at these T onset . Significant decomposition was detected at lower temperatures than T onset in all cases, meaning that the true ionic liquids stability is lower than that provided by the dynamic TG. Isothermal studies at lower temperatures than T onset were also carried out to estimate the long-term thermal stabilities at different temperatures.